Effect of Bifidobacterium longum subsp. infantis YLGB-1496 on common diseases in pediatrics: a randomized, blinded, placebo-controlled trial - Zhang, Xi; Chen, Ke; Lan, Hanglian; Chen, Haixia; Chen, Hua; Yang, Ping; He, Nianyang; Hung, Weilian; Zeng, Zaozhong; Liu, Changqi (Frontiers in Nutrition, 2025)
IntroductionRespiratory, gastrointestinal, and allergic diseases can significantly impact both the physical and mental health of children, affecting their overall quality of life. This study aimed to evaluate the preventive effects and safety of Bifidobacterium longum subsp. infantis YLGB-1496 in relation to respiratory, gastrointestinal, and allergic diseases in children.MethodsEligible healthy children were randomly assigned to either an intervention group (IG, n = 50), which received the probiotic, or a control group (CG, n = 50), which received a placebo, for a duration of 3 months. The primary outcome was the morbidity of upper respiratory tract infections (URTIs). Gut microbiota profiles were assessed via fecal 16S rRNA sequencing. Fecal immune biomarkers, including cytokines, immunoglobulins, and short-chain fatty acids (SCFAs), were measured to evaluate immune and metabolic responses.ResultsThe morbidity of URTIs over the 3-month intervention and follow-up period was significantly lower in the IG than in the CG. The incidence of upper respiratory tract infections (URTIs) over the 3-month intervention and follow-up period was significantly lower in the IG than in the CG, based on intention-to-treat (ITT) analysis [34.0% (17/50) vs. 58.0% (29/50), χ2 = 5.797, p = 0.016]. Per protocol (PP) analyses yielded similar results [36.2% (17/47) vs. 60.4% (29/48), χ2 = 5.59, p = 0.018]. YLGB-1496 supplementation significantly increased the relative abundance of Bifidobacterium bifidum, Bifidobacterium kashiwanohense PV2, and Bifidobacterium longum, while reducing Bacteroides thetaiotaomicron levels in the IG compared to the CG (p < 0.05). Additionally, YLGB-1496 reduced fecal levels of pro-inflammatory factors (IL-1β and IFNγ) levels, and increased levels of immunoglobulin (IgA, IgG, and IgM) and SCFAs (including butyric acid and total SCFAs).ConclusionDaily administration of YLGB-1496 at a dosage of 1.5 × 1010 CFU for 3 months significantly reduced the episodes of cough, fever, dry stool (defined as Bristol stool scale type 1–3), and eczematous changes of the skin. It also decreased the morbidity of URTIs, bronchopneumonia, and eczema, while beneficially modulating gut microbiome composition and immune function without any adverse effects.Clinical trial registrationhttps://www.isrctn.com/ISRCTN12824613, identifier: ISRCTN12824613.